Badan Akreditasi Nasional Industri Konstruksi Suatu Kebutuhan - Wibowo, Muhammad Agung; Hadihardaja, Joetata (MEDIA KOMUNIKASI TEKNIK SIPIL, 2006)
The construction industry has a significant role to the contribution of the development both in developed and developing countries.  The importance of the industry is not only in its product but also in the scale of the industry, its share in the national economy and how it affects society. Moreover, construction products, such as roads, bridges, railways, irrigation, schools, hospitals, dwellings, offices and factories are an important element in the economy and in improving living standards. An important issu of the construction industri in developing countries is to improve the quality of the industry due regard to social, envronment and sustainability aspect.  One of the alternative solution is to develop a Construction Industry Development Board (CIDB).  However, the detailed way in which all of aspects in the CIDB interact is not well understood.  This paper presents a possible system of CIDB model by using a prototype model from National Accreditation Body of Higher Education System.Keywords: construction industry development, government, CIDBPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3953[How to cite: Wibowo, M.A. dan Hadihardaja, J., 2006, Badan Akreditasi Nasional Industri Konstruksi Suatu Kebutuhan, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 3, pp. 277-286]